RANCANG BANGUN PERANGKAT PEMBANGKIT PWM BIPOLAR - Fathoni Fathoni (Politeknik Negeri Malang, 2018)
Electrical power settings, both AC and DC can be done by linear or switching. Controlled loads may be motors, heating elements or incandescent lamps. Generally the efficiency of load power control by way of switching is better than linear way so the way switching is widely used today. Switching also allows for automatic, remote and wireless control In load power management system with microcontroller, PWM generator circuit output is used for control of power switch. The output pulse can be TTL standard or with lower amplitude and on the control of the H bridge circuit required bipolar PWM with additional dead band on each side of the pulse ride. The bipolar PWM generator designed in this study has an output with TTL standard with a dead band circuit and a short circuit protection for VCC = 5 volts and a ground path, Testing with no load and short circuit in low and high output states is as follows. VOL(min) = 0.4 volts, VOH(max) = 4.2 volts. The short circuit of output to high GND is 100 mA and short circuit current to VCC path at low output is 90 mA, The output frequency of bipolar pulses is, 50, 100, 1k, 10k and 20k Hz with 10μs dead band